Atividade acaricida de plantas da família Annonaceae para Dermanyssus gallinae (De Geer) (Acari: Dermanyssidae) - Pares, Rafaela Barbosa (2019)
Dermanyssus gallinae is considered the most important hematophagous ectoparasite in poultry laying. Currently, it’s propagation control is only performed with chemical products, and in the majority, without registration in front of the competent organs. As a result there is the selection of resistant populations of mites and acaricidal residues in eggs. Thus, the research for alternatives, in this case, compounds produced by plants, which can be used to manage them, is necessary. Therefore, the object of this paper was to evaluate the acaricidal activity of soluble fractions in dichloromethane, obtained from methanolic extracts of Xylopia sericea (stem and fruit peels), X. emarginata (stem bark) and Duguetia lanceolata (stem bark) applied in D. gallinae. Farther, the most active fraction was chemically characterized. The species tested did not present fumigant activity for D. gallinae. However, all fractions on topical application were toxic to the mite. The most promising results were verified for the fraction of X. emarginata stem bark, with median lethal time (LT50) and median lethal concentration (LC50) of only 14 h and 331,769 μg/cm2, respectively. It is noteworthy that the concentration required to cause mortality in 50% of the mite population (LT50) was 73% lower than the positive control (cypermethrin). The exploratory chemical analysis of the fraction of X. emarginata (high-performance liquid chromatography coupled to tandem mass spectrometry - HPLC-MS/MS) and hydrogen nuclear magnetic resonance (1H NMR) revealed the presence of sesquiterpens as the major compound class, 9 suggesting that this chemical class belongs to the metabolite responsible for acaricidal activity